Religiosity, personality development and protective mechanism against disobedience: a review - Khairul Anwar Mastor,; Hasnan Kasan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper reviews selected articles on the role of religiosity in two main aspects: personality development and protective mechanism against disobedience. In the first part, several studies consistently found that religiosity and personality are highly correlated. Agreeableness and Honesty-Humility are two main personality characteristics that reflect the personality of religious people. These findings correspond to the existing literature on Islamic principle of akhlak vis-àvis personality that indicated the desirable and virtuous characteristics of people with faith. The second part is on the role of religiosity as a protective mechanism against various acts of disobedience. Reviews of selected work indicated that generally, higher religiosity cause the lower involvement in alcoholic drinking, tax evasion, depressive syndrome and drug usages. New studies on exploring the underlying process on causation effects of religiosity from Islamic perspective, on the personality development and as protective mechanism against different forms of disobediences are thus, strongly recommended.